Heavy Metals in Pig Livers; A Case of Munyaka Estate-Uasin-Gishu County, Kenya - Cherop, Cleophas K.; Otieno , Christina A.; Koskei , Peter (African Journal of Education,Science and Technology (AJEST), 2018)
have lead to alteration of their natural geochemical and biochemical cycle and balance. The risk of heavy metal contamination in meat/pork is of public health concern for both food safety and human health. The study aimed at determining the levels of lead, cadmium and mercury in pigs reared in two husbandry systems in Uasin-Gishu County, Kenya. A comparative cross-sectional study was employed. Thirty two pigs representing close to a thousand pigs in Munyaka estate were studied under two husbandry systems. Four branded manufactured feeds and 6 forage plants were analyzed by AAS machine for lead, cadmium and mercury. Results were summarized using means. The mean levels of lead, cadmium and mercury among intensively produced pigs were 0.10±0.04, 0.13±0.04 and 0.12±0.04mg/kg.wet weight respectively. The mean levels of lead, cadmiu and mercury in extensively produced pigs were 0.09±0.03, 0.18±0.05 and 0.14±0.09mg/kg.wet weight respectively. There was a significant difference (p<0.05) in cadmium levels in pigs under intensive and extensive husbandry system with extensively produced pigs having higher levels. Manufactured feed B had mean Pb levels of 0.26±0.01mg/kg.dry weight while feed D had Pb levels of 0.38±0.02mg/kg.dry weight. Cabbage leaves had mean Pb levels of 0.60±0.26 mg/kg.dry weight whereas grass on the roadside had mean Hg levels of 0.03±0.02mg/kg.dry weight with banana peelings also having mean Hg levels of 0.03±0.04mg/kg.dry weight. There was a significant difference (p<0.05) in cadmium levels in pigs under intensive and extensive husbandry systems with extensively produced pigs having higher levels. The study showed that pig livers under the study were not safe for human consumption due to the presence of mercury levels above the WHO maximum recommended levels. These metals are known to cause adverse health effects including neurological and renal disturbances neurological and renal disturbances. The Government shoul strictly enforce The Animal Diseases Act; Cap364 on prohibition of extensive husbandry system. Kenya bureau of standards (KEBS) and Department of Veterinary Services (DVS) should regularly monitor and evaluate pork to safeguard human health. Farmers should be educated on the need to discriminately use of Phosphatic fertilizers and pesticides as they contribute to HMs in the soil and the consequent uptake by plants.